P1276EXPLORING POSSIBLE PREDICTORS OF STRUCTURAL DETERIORATION AFTER TRANSCATHETER AORTIC VALVE IMPLANTATION IN HEMODIALYSIS PATIENTS. (6th June 2020) - Masuyama, Satoshi; Mizui, Masayuki; Maeda, Koichi; Kuratani, Toru; Sakaguchi, Yusuke; Sakata, Yasushi; Sawa, Yoshiki; Isaka, Yoshitaka
Abstract: Background and Aims: Transcatheter aortic valve implantation (TAVI) is an effective treatment for aortic stenosis (AS) in high-risk patients, such as those who are suffering ESRD on hemodialysis. We previously showed that long-term survival of hemodialysis patients underwent TAVI was lower than that of non-hemodialysis patients but was comparable with that of hemodialysis patients treated with surgical aortic valve replacement. It is known that hemodialysis is a high risk of the bioprosthetic structural valve deterioration (SVD) after valve replacement surgery. Consistently, higher incidence of re-TAVI operation due to restenosis was observed in hemodialysis patients than in non-hemodialysis patients (Odds ratio [OR]:29.4, p<0.001). In this study, we aimed to identify predictors of SVD in post-TAVI hemodialysis patients. Method: From April 2012 to December 2015, 24 patients on hemodialysis were selected to receive TAVI for the treatment of AS in Osaka University Hospital. Demographic and laboratory data at pre- and post-operation were compared between patients who underwent re-TAVI (valve-in-valve) (SVD group) and those who did not (no-SVD group). Results: During the follow-up period (maximal 7 years), 4 out of 24 patients required re-TAVI (valve-in-valve) operation because of SVD. Although serum calcium, phosphate, and PTH levels before operation were comparable between SVD group and no-SVD group, serum magnesium levels were significantly lower in SVD group. Lower serum magnesium quartiles were associated with a higher risk of SVD (OR 5.83, p=0.036). While effective orifice area index (EOAi) of aortic valve at 1 week after TAVI was similar between the 2 groups, EOAi improvement at 1 month was significantly poorer in SVD group than in no-SVD group (1.70 ± 0.15 vs 2.50 ± 0.56, p = 0.049). Conclusion: The higher incidence of re-TAVI due to SVD in hemodialysis patients could be related with pre-operative low magnesium levels and with one-month post-operative low EOAi improvement. This was a single center observational study, and the number of patients was very small so that our data would not be necessarily applicable for every patient. Further investigation is necessary for identifying a prognostic predictor of SVD, which will lead to the prevention of unfavorable re-operation in hemodialysis patients.